Ingleses pretos, barbadianos negros, brasileiros morenos?: identidades e memórias (Belém, séculos XX e XXI) - LIMA, Maria Roseane Corrêa Pinto (2006)
It deals about black people immigration from British Caribbean Islands to Belém, which occurred in the first decades of the 20th century, more precisely of those who were generally called Barbadians (barbadianos). It discusses the contours of this identification in Belém and analyses the life stories of the descendants of the second and third generations. It aims to discuss in which contexts and situations the signs of their identifications were manipulated to mark distinctions, by them and by others. In order to do this, it considers the symbols (of prestige and stigma) of the British, Brazilian and Barbadian identities, when they were related one to the other, and passed through by the process of demarcation of alterity, but also by the racism.